Fog-Based Secure Chaotic Wireless Sensor Network for ECG Data Transmission in Healthcare Systems - Ponugoti Kalpana; N. Subhash Chandra; Maddala Vijayalakshmi; Sushma Polasi; Sarangam Kodati; M. Dhasaratham; Jagadesh Gona (International Journal of Computational and Experimental Science and Engineering, 2025)
The continuous monitoring and transmission of electrocardiogram (ECG) data are essential for the proactive and responsive management of cardiovascular health, particularly in remote and connected healthcare systems. However, ensuring the secure and efficient transmission of this highly sensitive data over Wireless Sensor Networks (WSNs) remains a significant challenge due to the risks of data interception and the need for low-latency processing. This research introduces a novel architecture, the Fog-Based Secured Chaotic Wireless Sensor Network (WSN), specifically designed to address these challenges by integrating fog computing with chaotic encryption methods to enhance data security and efficiency. In this system, fog nodes positioned at the network’s edge serve as intermediary processors, performing pre-processing, data encryption, and storage functions before the data is transmitted to central servers. This approach reduces reliance on cloud infrastructure and minimizes data transmission time, which is critical for real-time applications. The results reveal that the proposed framework enhances data transmission security and achieves a 30% latency reduction examined to conventional cloud-based systems. This fog-based chaotic WSN framework provides a scalable, secure, and efficient solution for ECG data transmission, meeting the evolving demands of connected healthcare and real-time patient monitoring applications.